2017
DOI: 10.1021/acsami.7b00810
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Protein and Peptide Functionalization of Single-Walled Carbon Nanotubes for Biodelivery and Optical Sensing Applications

Abstract: ABSTRACT:The exquisite structural and optical characteristics of single-walled carbon nanotubes (SWCNTs), combined with the tunable specificities of proteins and peptides, can be exploited to strongly benefit technologies with applications in fields ranging from biomedicine to industrial biocatalysis. The key to exploiting the synergism of these materials is designing protein/peptide-SWCNT conjugation schemes that preserve biomolecule activity while keeping the near-infrared optical and electronic properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
168
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(171 citation statements)
references
References 106 publications
(208 reference statements)
0
168
0
3
Order By: Relevance
“…We employed NIR hyperspectral fluorescence microscopy to assess the chirality-resolved intracellular stability of the (GT)n-SWCNTs [15]. Using a 730 nm excitation laser, we were able to resolve four distinct bands in the NIR region corresponding to the emission spectra of the four brightest SWCNT chiralities, (10,2), (9,4), (8,6), and (8,7) ( Fig. S1a,b) [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed NIR hyperspectral fluorescence microscopy to assess the chirality-resolved intracellular stability of the (GT)n-SWCNTs [15]. Using a 730 nm excitation laser, we were able to resolve four distinct bands in the NIR region corresponding to the emission spectra of the four brightest SWCNT chiralities, (10,2), (9,4), (8,6), and (8,7) ( Fig. S1a,b) [15].…”
Section: Resultsmentioning
confidence: 99%
“…Their electronic band gap energies are dependent on their chiral identity, denoted by integers (n,m), and vary based on diameter and rollup angle [4], resulting in semiconducting species which exhibit band gap photoluminescence [3]. Although highly hydrophobic in their raw as-produced form, non-covalent functionalization of SWCNTs using surfactants [5,6] or amphiphilic biomolecules [7][8][9] has been shown to effectively disperse SWCNTs into aqueous solutions while preserving their intrinsic optical properties. Single-stranded DNA can non-covalently functionalize SWCNTs via -stacking of hydrophobic bases onto the SWCNT sidewall, while the hydrophilic phosphate backbone allows for significantly enhanced aqueous solubility [10].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Various peptides with these unique characteristics enabling them to bind to specic materials are used as non-covalently bound linkers for material surface modication. 6,7 In addition to their usage for material surface modications, peptides can bind to various targets including bacterial cells. Because of increasing worldwide concerns about pathogenic bacteria, particularly drug-resistant bacteria, bacterial recognition probes are gaining attention as tools for microbial detection.…”
Section: Introductionmentioning
confidence: 99%
“…Here,finetuning of the experimental parameters is crucial to prevent colloidal instability resulting from the conjugation of too many nanobodies to the SWCNT surface.T his colloidal stability is ak nown and important, but still often neglected factor in research on peptide-or protein-modified SWCNTs. [24] Using the optimized GBP/SWCNT-(GT) 20 ratio,t he conjugates were still stable even after more than six weeks of storage at 4 8 8C( see Figure S3). Figure 1b shows the retained nIR fluorescence properties after conjugation of the GFP-binding nanobody upon excitation at 561 nm compared to the unconjugated sample.T oprove the successful conjugation of GBP (4)t ot he SWCNT,w ee mployed DNA-and protein-stained sodium dodecylsulfate polyacrylamide gel electrophoresis (SDS-PAGE) ( Figure 1c).…”
mentioning
confidence: 99%
“…GFP is av aluable target because al arge number of transgenic organisms and cells are available with GFP-tagged proteins. Noncovalent functionalization is used in order not to alter or destroy the nIR fluorescence of SWCNTs, [21][22][23][24][25] although recently Setaro et al also reported ac ovalent modification strategy preserving the nIR fluorescence. [26] While there are many different noncovalent functionalization concepts available, [21,27,28] DNA/SWCNTs have the additional advantage that they can be used for the sensing of small molecules.…”
mentioning
confidence: 99%